HUBUNGAN FAKTOR SOSIODEMOGRAFIS DAN FAKTOR KEHAMILAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSIA SRI RATU MEDAN TAHUN 2014 - dian sari zendrato; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Low birth weight infant is a newborn baby whose weight at birth less than 2500 gram regardless of gestational age. Low birth weight infant contributes to neonatal mortality as an indicator of a nation's community health status. World Health Organization (WHO) in 2010 reported a prevalence of low birth weight infant in the world in the period 2005-2010 is 15%. In Indonesia, the prevalence of low birth weight infant in 2013 is 10.2%. To determine the sociodemographic factors and pregnancy associated with low birth weight infant in RSIA Sri Ratu Medan in 2014 conducted the study with a population of 874 people and the sample totaled 106 data of mothers who gave birth in RSIA Sri Ratu Medan. This research is an analytic survey with cross sectional design was followed by univariate and bivariate analyzes. The results showed there are three variables that relate in the incidence of low birth weight is the work of women (p = 0.003), history of maternal disease (p = 0.032) and gestational age (p = 0.001). Other variables that maternal age (p = 0.084), spacing pregnancies (p = 0.628), parity (p = 0.398), maternal education (p = 0.074), and complications of pregnancy (p = 0.227) had no significant difference with  low birth weight infant.  The conclusion from this study that there is an employment relationship mother, maternal medical history, and gestational age with low birth weight infant in RSIA Sri Ratu Medan in 2014. No relation between  maternal age, parity, spacing pregnancies, maternal education and pregnancy complications with low birth weight infant in RSIA Sri Ratu Medan in 2014. Health workers are expected to provide counseling for pregnant women about the risks of low birth weight and impact caused by the LBW . For pregnant women are expected to plan properly pregnancy , especially in terms of age during pregnancy , reduced physical activity that can interfere with pregnancy , a routine check-up to prevent complications of the disease history has ever experienced , as well as maintain a healthy pregnancy so that pregnancy can achieve the right time. The hospital is expected to complete the recording of the card status in the capital such as hemoglobin levels. Keywords: low birth weight, sociodemographic and pregnancy factors, RSIA Sri Ratu Medan